Implementation and spread of a simple and effective way to improve the accuracy of medicines reconciliation on discharge: a hospital-based quality improvement project and success story. Issue 3 (1st August 2019) - Botros, Shady; Dunn, John
Abstract : Background: Changes are often made to medications at times of transitions in care. Inadequate reconciliation during admission, transfer and discharge causes medication errors and increases risks of patient harm. Despite well-established multidisciplinary medicines reconciliation (MR) processes at hospital admission, our MR process at discharge; however, was poor. The main errors included failure to recommence withheld medicines and lack of documentation explaining changes made to medications on discharge. Our objective was to develop an intervention that supports prescribers to follow a simple standardised MR process at discharge to reduce these errors. Methods: Working closely as a multidisciplinary team, we used improvement methodologies to design and test a process that reliably directs prescribers in surgery to use the inpatient prescribing chart as well as the MR on admission form as sources to create accurate discharge prescriptions. The project was segmented into testing, implementation, spread and sustainability. Results: The tested intervention helped the accuracy of discharge prescriptions steadily and quickly improve from 45% to 96% in the pilot ward. Following the successful implementation and sustainability in two separate pilot wards, the intervention was spread to the remaining eight wards producing a similar improvement. Conclusions: To improve patient safety, it is crucial to ensure that information about medicines is effectively communicated when care is transferred between teams. Although this can be challenging, we've shown that it can be done effectively and reliably if this responsibility is equally shared by healthcare professionals from all disciplines while being supported by safe systems that make it easy to do the right thing. Successfully implementing a standardised multidisciplinary MR process at discharge can also reduce the reliance on pharmacists therefore freeing them to undertake other clinical roles.